Polyethylene glycol modified-carbon nanotubes as materials for biomedical applications : In vitro and in vivo sub-acute toxicity evaluation - Muhammad Redza, Mohd Radzi; Yong, Sin Yee; Mock, Phooi Yan; Nur Amanina, Johari; Wan Fatin Amira, Wan Mohd Zawawi; Faridah, Aminullah Lubis; Nur Afrina, Muhamad Hendri; Santhana, L. Raj; Khairunadwa, Jemon (Elsevier B.V., 2022)
Multiwalled-carbon nanotubes (MWCNTs) serve as one of the popular options for biomedical applications. Nonetheless, MWCNTs toxicity and biosafety are concerned, particularly on their aggregation after systemic distribution, necessitating modification. Although there was evidence of the toxicity of MWCNTs in the literature, the inconsistent parameters reported by each study, however, provide limited information to claim the sub-acute toxicity caused by MWCNTs. Thus, the present study aims to evaluate the subacute toxicity of modified MWCNTs, both in vitro and in vivo. In this study, polyethylene glycol-MWCNTs (PEG-MWCNTs) were characterized by standard characterization analysis. Exposure of PEG-MWCNTs on normal human fibroblast cells in vitro exhibited a high percentage of cell viability while in vivo assessment demonstrated no significant changes in rats’ behavior, body weight and serum biochemical analysis. Moreover, organ histological analysis indicated no significant changes following PEG-MWCNTs administration. No-observed-adverse-effect-level (NOAEL) value from this study was determined at 4 mg/kg. Results from this study suggested that modified MWCNTs induced minimal toxicity effect following systemic delivery in rats, thus, could be an excellent material for biomedical applications.